PENGARUH PENERAPAN METODE AKUNTANSI PERSEDIAANTERHADAP MARKET VALUE PERUSAHAAN PADA EMITEN DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2013)
This study aimed to determine the effect of the application of the method of accounting for inventories to market value of companies listed on the Stock Exchange.The population in this study is a manufacturing company that uses the FIFO method and the average in 2008-2011. The samples were taken by purposive sampling method. Data were analyzed using multiple linearr egression analysis.The results in this study is the application of FIFO Method of Inventory Accounting Impact on Financial Statements in theCompany's Market Value Against Discrimination Approach approach, it dijunjukkan adjusted R² values greater than the FIFO Inventory Accounting Method Average. Implementation of Inventory Accounting Method Average Impact on Financial Statements in the Company's Market Value Of Discerning Approach approach using the Davidson-MacKinnon J test TestKeywords: Inventory Accounting Method, Market value.